Genetic analyses are more sensitive than morphological inspection at detecting the presence of threatened Mojave desert tortoise (Gopherus agassizii) remains in canid scat and raven pellets. Issue 6 (7th April 2022) - Parker, Lillian D.; Quinta, Jessica D.; Rivera, Isabel; Cypher, Brian L.; Kelly, Erica C.; Campana, Michael G.; Fleischer, Robert C.; Boarman, Ryan; Boarman, William I.; Maldonado, Jesús E.
Abstract: Subsidization of predator populations increases predation pressure on prey species, which is exacerbated when natural resources are scarce. Estimating the frequency of predation by subsidized predators on vulnerable species, especially low‐density, long‐lived species such as the federally threatened Mojave desert tortoise ( Gopherus agassizii ), allows landscape managers to evaluate the need for actions like reducing subsidies, discouraging predation by taste aversion, or predator removal. Most studies of Mojave desert tortoise predation have relied on morphological analysis to identify hard parts in predator scat. Here, we developed and validated a qPCR assay to test for the presence of Mojave desert tortoise in DNA extracted from scat and pellets. We used the assay to detect tortoise DNA in scat and pellets collected in a conservation easement adjacent to Boulder City, Nevada, from three Mojave desert tortoise predators: coyotes ( Canis latrans ), desert kit foxes ( Vulpes macrotis arsipus ), and common ravens ( Corvus corax )—all of which consume anthropogenic resources. We compared the results of our qPCR assay to results from morphological analysis of the same samples and found that the qPCR method is much more sensitive at detecting the presence of tortoise remains. Although neither method can determine whether consumption was the result of predation or scavenging, nor how many individual tortoises were consumed, our findings indicate that conservation managers may benefit from focusing efforts on reducing subsidies that attract and support predators and on reducing tortoise mortality from predation. Abstract : Coyotes, desert kit foxes, and ravens are all known to consume anthropogenic resources and their populations can be subsidized by these resources. Subsidized populations can, in turn, exert higher predation pressure on prey species. We designed and implemented a qPCR method to detect Mojave desert tortoise remains in canid scat and raven pellets, and compared rates of detection between the qPCR method and the traditional morphological analysis of hard parts method. We found that the qPCR method was more sensitive at detecting tortoise remains in excrement. Although neither the qPCR method nor the morphological method can reveal how many tortoises were consumed or if consumption was the result of predation or scavenging, the larger number of qPCR‐positive scats and pellets is consistent with a hypothesis of higher consumption than indicated by hard parts analysis. This result suggests that landscape managers in the Mojave Desert could improve conservation of the desert tortoise by focusing efforts on reducing the presence of anthropogenic resources that can attract and sustain predators, as well as on limiting predation by conditioned taste aversion. In the future, our study can be replicated and extended to evaluate the effects of management practices on tortoise consumption.